A Sarong rolled around a body demonstrates that the force for separating two sheets joined by folding and rolling is very large. (21st September 2020) - Akbar, Fathan; Abdullah, Mikrajuddin
Abstract: A lot of new science has been inspired by common phenomena and even by old traditions practiced in our daily lives. Eventually, after deep exploration, this may engender unexpected new technologies. In this paper, inspired by the wearing of a traditional cloth called a sarong, by the community in South East Asian countries and others, we investigate the behavior of sheets folded in the same way as the rolling of the sarong around the stomach. Simple equipment was designed to qualitatively collect the data which was combined with simple modeling. The rolling of the sarong around the stomach generates a joining force between two sheets, increasing proportionally to the square of the number of rolls. This finding can potentially be applied for developing a method for strongly joining sheets by simply rolling them and releasing the join by unrolling. This work can also be simply duplicated elsewhere, so it is worthy of teaching materials at undergraduate level. Both the scientific and the teaching contents can be extracted simultaneously.